Life expectancy, life disparity, and differential racialization among Chinese, Asian Indians, and Filipinos in the United States - Darwin A. Baluran (Elsevier, 2023)
This article advances differential racialization as a lens to frame health disparity trends within the Asian racial category. Using formal demographic methods, I analyzed data from the Multiple Cause of Death File and the American Community Survey to examine the trends in life expectancy and life disparity among Chinese, Asian Indians, and Filipinos in the United States between 2005 and 2019. While Chinese, Asian Indian, and Filipino life expectancy oscillated between each period under study, those oscillations contributed to an overall widening advantage for Chinese over their Asian Indian and Filipino counterparts. I posit that widening inequalities between the three groups are suggestive of their increasingly disparate racial statuses. These findings underscore the importance of contextualizing disaggregated health data within the social conditions that produce inequalities, namely race/racialization/racism.